Avaliação ergonômica em estações de trabalho no parque zoológico municipal de Bauru/SP e na Fundação Jardim Zoológico da Cidade do Rio de Janeiro/RJ - estudode caso de tratadores de felinos de grande porte. - Amaral, Fernando Periard Gurgel do (2002)
Zooiogical gardens are important institutions to gather data for the ex situ study of wiid animais. For such, a relationship between captive species and man, be it for feeding, cleaning, or transportation purposes or stili due to other duties, is necessary Some of these duties are of imminent danger to the worker dealing with the animais, and rnight be even iethal. Besides other professionals the animal keeper is the one that has most contact with the animais. The proposal is based on work ergonomic evalution - WEE, in response to the anomalies which determine security as weii as physicai and mental confort problems, based on the analysis of the actual work. WEEs were made in two zoological gardens, the Fundação RioZoo/RJ and the Zoo Bauru/SP, at working stations sheltering big felines (Panthera tigris altaica and Panthera leo). One animal keeper was chosen at each institution and he has beeri analysed when carring-out his duties reiated to these animais. By means of filmings, interviews and physical measurements an anaiysis was made to propose interventions such as the improvement of intemai Iight, adequation to EPI, training programs, maintenance plans, among other. The institutions reacted weli regarding carring-out the interventions proposed. However, they depend on budget in order to impiement such proposais. Foilow-up of said proposais wiil be made, whenever possivel, based on the registers also proposed in these scenarios scope.